Pengembangan Assessment as, for, dan of Learning dalam Pembelajaran Pendidikan Agama Islam: Studi Literatur - Desni Mardiah; Tasman Hamami (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
Assessment plays a crucial role in Islamic Religious Education (PAI) learning, as it not only measures student learning outcomes but also supports and enhances the quality of the learning process. In the context of modern education, assessment is expected to develop students' competencies holistically, encompassing the cognitive, affective, and psychomotor domains. Therefore, integrating Assessment as Learning (AaL), Assessment for Learning (AfL), and Assessment of Learning (AoL) approaches is crucial to creating a more meaningful, student-oriented PAI learning process. This study aims to analyze the concepts of AaL, AfL, and AoL and identify assessment development strategies that align with the characteristics of PAI learning. The method used is a literature review that analyzes relevant sources, including books, scientific journal articles, and prior research on assessment in Islamic Religious Education and learning. The results of the study indicate that AaL emphasizes self-reflection and active student involvement in the learning process; AfL serves as formative assessment, providing continuous feedback to monitor students' learning progress; and AoL serves as a summative assessment to evaluate learning outcomes at the end of the learning process. Furthermore, assessment development in Islamic Religious Education (PAI) learning can be achieved through authentic assessments, a values- and character-based approach, the use of learning technology, and integration with project-based learning. These strategies enable assessment to function not only as an evaluation tool but also as a means of enhancing students' understanding and developing character aligned with Islamic values.